The Concept Mapping in Learning Strategies: an Experimental Study of the Effect of Learning Strategies and the Attitude of the Students Towards Subjects and Ethical Learning Outcomes - Abidin Arief, Zainal; Firdaus Alviansyah Rinjani, Ilham; ., . (International Journal of Engineering and Technology, 2018)
The objective of this research is to find out the effect of learning strategies and the attitude of students on the Ethics course and its learning outcomes. The research is conducted to the students (n=84) of The School of Politics Djuanda University Bogor. It is applied an experiment of 2 x 2 factorial designs. The results of this research are: (1) The students learning outcomes of the course by using concept mapping strategy is higher than those who used conventional strategy; (2) The learning outcomes of the students with positive attitude and used the concept mapping is higher than those who used conventional strategy; (3)The students with negative attitude, and used the concept mapping is lower than those who used conventional strategy; (4) There is an interaction effect between learning strategy and attitude toward studentsâ€™ learning outcomes of the course of public administration Ethics. Learning outcomes of students who have positive attitude toward the course of Public Administration Ethics can be improved by using concept mapping learning strategies. Â Â